2011
DOI: 10.1016/j.gmod.2010.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Sketch-based warping of RGBN images

Abstract: While current image deformation methods are careful in making the new geometry seem right, little attention has been given to the photometric aspects. We introduce a deformation method that results in coherently illuminated objects. For this task, we use RGBN images to support a relighting step integrated in a sketch-based deformation method. We warp not only colors but also normals. Normal warping requires smooth warping fields. We use sketches to specify sparse warping samples and impose additional constrain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Therefore, if F (p) < 0, it is an anticline, otherwise it is a syncline. In this work we chose the Hermite-Birkhoff Radial Basis Function (HBRBF) interpolation [Pereira et al 2011] as our function F . HBRBFs create implicit surfaces that can interpolate: values, gradients, or values and gradients at a point in space, which is a good fit for our problem of interpolating contacts and dip directions.…”
Section: D Geologic Model Creationmentioning
confidence: 99%
“…Therefore, if F (p) < 0, it is an anticline, otherwise it is a syncline. In this work we chose the Hermite-Birkhoff Radial Basis Function (HBRBF) interpolation [Pereira et al 2011] as our function F . HBRBFs create implicit surfaces that can interpolate: values, gradients, or values and gradients at a point in space, which is a good fit for our problem of interpolating contacts and dip directions.…”
Section: D Geologic Model Creationmentioning
confidence: 99%
“…1). Olsen et al (2009) and Pereira et al (2011) demonstrated the application of SBIM to general computer-aided design problems. Natali et al (2014) created geological models by sketching stratigraphic layers according to their depositional and erosional history.…”
Section: Introductionmentioning
confidence: 99%
“…Sketch-based interface and modelling (SBIM) is an approach for rapid model creation that is used for prototyping in many nongeological CAD and CFD applications (e.g. Olsen et al 2009Olsen et al , 2011Pereira et al 2011). SBIM allows model concepts to be rapidly sketched and tested.…”
mentioning
confidence: 99%